PROSAMIM – BID UMA EXPERIÊNCIA DE REASSENTAMENTO DE PESSOAS - Dutra, Viviane Alves da Silva (2018)
The objective of this research was to analyze the resettlement in the areas of intervention of Prosamim, from the perspective of the Involuntary Resettlement Policy - OP710, of the InterAmerican Development Bank - IDB. Seeking to highlight aspects such as: community organization, socio-environmental and cultural changes from the new housing condition to verify the efficiency of the application. The methodology, observation and focus groups made it possible to evaluate several factors, but to analyze the efficiency of the OP 710 it would be necessary to check for longer periods of time. However, in terms of execution, it is recorded that the main difficulty for the efficiency of the OP 710 is the way the implementation takes place. In the speeches it is shown that the points of greatest psychological and moral suffering were due to management problems that compromised the objectives recommended. There is concern about the replacement of housing and mitigation of losses related to resettlement, however, it is pointed out the need for dialogue and expansion of community participation. It was verified that in the perspective of the program the marginality and the environmental degradation are bigger or more urgent than socio-cultural aspects what leads to. The need to reflect, therefore, the interventions in Manaus, are mostly prepared in a superficial and compulsory way. Even when describing care in mitigating the impacts, the result will be restricted, if applied without actually providing participation and citizenship.